H∞ control for nonlinear time-varying delay systems with convex polytopic uncertainties - P. Niamsup (2018)
This paper investigates H∞ control for a class of nonlinear systems with time-varying delays and convex polytopic uncertainties. A new type of parameter-dependent Lyapunov-Krasovskii functional is introduced to derive delay-dependent sufficient conditions for the H∞ optimal control with exponential stability. All the conditions developed in this paper are formulated in terms of linear matrix inequalities. Finally, a numerical example shows the effectiveness of the proposed methodology. © 2010 Elsevier Ltd. All rights reserved.